Cystic Meningioma (Bangladesh Journal of Medical Science, 2013)
Meningiomas are most common intracranial extraaxial tumours, but atypical meningeiomas like cystic meningioma are rare. It is about 2 to 4 % in adults and 10 to 19 % in infants. Because of its atypical presentation a case of cystic meningioma is presented. DOI: http://dx.doi.org/10.3329/bjms.v12i1.11542 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.83-85